Bank Lending under Macroeconomic Instability: Analysis of the Situation in Kazakhstan - TALIMOVA, Lyazat; KALKABAYEVA, Gauhar (Journal of Advanced Research in Law and Economics; Vol 8 No 4(26) (2017): JARLE Volume 8 Issue 4(26) Summer 2017, 2017)
In the article, we take into consideration the main trends of development of bank crediting of the economy of the Republic of Kazakhstan in modern conditions. Factors that have had a negative impact on the indicators of credit activity of Kazakhstan banks are revealed. A comparative analysis of the ratio of loans to the private sector in the volume of GDP in the group of countries studied was carried out. The quality of the loan portfolio of second-tier banks, the structure of overdue loans on bank loans was assessed. The indicators of the share of overdue loans in Kazakhstan, Russia and Belarus are analyzed. The problem of the discrepancy between the forecasted values of the volume of bank loans and the actual ones is revealed. The economic-mathematical model of forecasting the volumes of bank lending in the Republic of Kazakhstan is considered.